Adaptive Leadership in the Governance of Investment Improvement in Central Mamuju Regency - Andi Muhammad Aslamsyah; Badu Ahmad; Muhammad Akmal Ibrahim; Didik Iskandar (Journal Social Civilecial, 2025)
Adaptive leadership in investment enhancement governance in Central Mamuju Regency still faces various obstacles in responding to changing regional investment needs. This condition causes investment governance to still be unable to operate responsively and sustainably. This study aims to analyze adaptive leadership in investment enhancement governance in Central Mamuju Regency. This study uses a qualitative exploratory approach with a case study method. Data were collected through in-depth interviews, observations, and documentation of local governments and business actors. Data analysis uses an interactive model through the stages of data reduction, data presentation, and conclusion drawing. The results show that regional heads have attempted to build policy flexibility, transparent communication, service innovation, adaptability, collaboration, investment development vision, and resilience in regional investment governance. However, the implementation of adaptive leadership remains suboptimal because cross-sector coordination, service innovation, and responsiveness to business needs still face various bureaucratic and institutional obstacles. This condition causes regional investment governance to still be unable to operate quickly, responsively, and adaptively to changing regional development needs. This study concludes that adaptive leadership in investment enhancement governance still needs to be improved by strengthening cross-sector communication, investment service innovation, accelerating response to business needs, and strengthening the direction of more adaptive and sustainable regional investment development.